School paths, migration and teacher training: processes in dialogue (Revista INTEREDU11, 2022)
This research paper studies the school trajectories of Bolivian women who are currently residing in Ushuaia, Argentina, in Tierra del Fuego, and had been part of the local teacher-training process, in that city. An investigation was proposed from a socio-anthropological perspective (Achilli, 2005) with a flexible design which have allowed us to provide an in-detail description of how such phenomena, inscribed in broad sociocultural matrices, are both configured and manifested. From this research, we can say that the experiences lived by these migrant women, who have also faced a pedagogy-training process, favored the construction of new meanings regarding the material and symbolic conditions of their school trajectories, enabling new settings to transform them.